2021
DOI: 10.5194/acp-21-13455-2021
|View full text |Cite
|
Sign up to set email alerts
|

In situ observation of new particle formation (NPF) in the tropical tropopause layer of the 2017 Asian monsoon anticyclone – Part 2: NPF inside ice clouds

Abstract: Abstract. From 27 July to 10 August 2017, the airborne StratoClim mission took place in Kathmandu, Nepal, where eight mission flights were conducted with the M-55 Geophysica up to altitudes of 20 km. New particle formation (NPF) was identified by the abundant presence of nucleation-mode aerosols, with particle diameters dp smaller than 15 nm, which were in-situ-detected by means of condensation nuclei (CN) counter techniques. NPF fields in clear skies as well as in the presence of cloud ice particles (dp > … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 96 publications
(172 reference statements)
1
4
0
Order By: Relevance
“…Together with the single particle measurements, we thus have several indications suggesting that the ATAL composition is to a large part controlled by secondary organic and inorganic aerosol formation. Our findings complement concurrent in situ observations of particle microphysical properties by Mahnke et al (2021) and Weigel et al (2021b), demonstrating that new particle formation and subsequent particle growth by condensation and coagulation takes place in the lower ATAL region below the tropopause (see Fig. 3).…”
Section: Secondary Organic and Inorganic Particles Within The Atalsupporting
confidence: 84%
See 1 more Smart Citation
“…Together with the single particle measurements, we thus have several indications suggesting that the ATAL composition is to a large part controlled by secondary organic and inorganic aerosol formation. Our findings complement concurrent in situ observations of particle microphysical properties by Mahnke et al (2021) and Weigel et al (2021b), demonstrating that new particle formation and subsequent particle growth by condensation and coagulation takes place in the lower ATAL region below the tropopause (see Fig. 3).…”
Section: Secondary Organic and Inorganic Particles Within The Atalsupporting
confidence: 84%
“…3, which is a comprehended representation of the data from their studies, and which shows the results of particle number concentration larger than 10 nm and larger than 65 nm as a function of altitude and potential temperature. In these publications and in Weigel et al (2021b) it was demonstrated that new particle formation and subsequent particle growth by condensation and coagulation can be frequently observed in the lower ATAL region below the tropopause (between 355 and 370 K). Note however, that COPAS data for particles between 6 and 10 nm in diameter -indicative of such transient new particle formation events -are not included in Fig.…”
Section: Chemical Composition Of the Atal Aerosol Particles As Measur...mentioning
confidence: 94%
“…Information on these parameters is critically needed for improving model representation. The StratoClim campaign obtained the first significant set of airborne in situ and remote‐sensing aerosol data in the ATAL (Höpfner et al., 2019; Mahnke et al., 2021; Weigel, Mahnke, Baumgartner, Dragoneas, et al., 2021; Weigel, Mahnke, Baumgartner, Krämer, et al., 2021) from Kathmandu‐based research flights. These measurements sampled the South Asian region including Nepal, Pakistan, northern India, and the Bay of Bengal.…”
Section: Chemical Trace Gas and Aerosol Content Within The Eddy Shedd...mentioning
confidence: 99%
“…The TTL, which extends over an altitude range from about 14 to 18 km in this area, acts as a "gateway to the stratosphere" (Fueglistaler et al, 2009), as air from this region can be transported into the lower stratosphere via diabatic ascent (Garny and Randel, 2016). With the transport of climate-relevant natural and anthropogenic trace gases, water vapor, and aerosol particles into the stratosphere, precursor gases also enter the UT-LS, which can lead or contribute to the formation of new particles from the gas phase (new particle formation -NPF) (Brock et al, 1995;Weigel et al, 2011;Williamson et al, 2019). Asia is currently one of the regions with the highest emission of atmospheric sulfur worldwide.…”
Section: Introductionmentioning
confidence: 99%